¿Cuento contigo? La estabilidad en la gestión de César Álvarez (2006-2013) - Arévalo León, Rosa (Pontificia Universidad Católica del Perú, 2015)
This article analyzes the factors that contributed to Cesar Alvarez’s administration stability as regional president of Ancash during almost two full consecutive terms (2006 – 2013). Thus, the research focuses on the development of clientelistic and patronage networks that strength- ened his ties with citizens, providing him with constant support. Moreover, those practices protected him from any act of fiscalization or investigation. Finally, public spending, largely financed with mining canon, made possible for Alvarez to show himself as an efficient regional president by developing major infrastructure projects in the region.

El presente artículo se centra en los factores que dieron estabilidad a la gestión del expresidente regional de Áncash,  César Álvarez,  durante casi dos periodos consecutivos (2006- 2013) y con probables miras hacia uno tercero. De esta manera, la investigación se enfoca en el desarrollo de redes clientelares y de patronazgo que fortalecieron los nexos que estableció con la ciudadanía, proporcionándole apoyo constante. Asimismo, aquellas prácticas le sirvieron de blindaje ante cualquier acto de fiscalización o investigación. Por último, el gasto público en gran parte producto del canon minero, hizo que Álvarez se demuestre como una autoridad eficiente alpromocionar grandes obras de infraestructura -sobrevaloradas- en la región.
Can I count on you? The stability of Cesar Álvarez’s administration (2006 - 2013)
Keywords: Politics; Subnational Authoritarianism; Clientelism; Patronage; Public Spending; Corruption; Autoritarismo Subnacional; Clientelismo; Patronazgo; Gasto Público; Corrupción; Diezmo; https://purl.org/pe-repo/ocde/ford#5.06.00